Non-Invasive Monitoring of Core Body Temperature for Targeted Temperature Management in Post-Cardiac Arrest Care - Fiorini, Kyle; Tamasi, Tanya; Dorie, Justin; Hegazy, Ahmed F.; Lee, Ting-Yim; Slessarev, Marat (Frontiers in Medicine, 2022)
Importance: Accurate monitoring of core body temperature is integral to targeted temperature management (TTM) following cardiac arrest. However, there are no reliable non-invasive methods for monitoring temperature during TTM. Objectives: We compared the accuracy and precision of a novel non-invasive Zero-Heat Flux Thermometer (SpotOn) to a standard invasive esophageal probe in a cohort of patients undergoing TTM post cardiac arrest. Design, Setting and Participants: We prospectively enrolled 20 patients undergoing post-cardiac arrest care in the intensive care units at the London Health Sciences Centre in London, Canada. A SpotOn probe was applied on each patient’s forehead, while an esophageal temperature probe was inserted, and both temperature readings were recorded at 1-minute intervals for the duration of TTM. Main Outcomes and Measures: We compared the SpotOn and esophageal monitors using Bland-Altman analysis and Pearson correlation, with accuracy set as a primary outcome. Secondary outcomes included precision and correlation. Bias exceeding 0.1°C and limits of agreement exceeding 0.5°C were considered clinically important. Results: Sixteen (80%) of patients had complete data used in the final analysis. The median (interquartile range) duration of recording was 38 (12-56) hours. Compared to the esophageal probe, SpotOn had a bias of 0.06 ± 0.45ºC and 95% limits of agreement of -0.83 to 0.95 ºC. Pearson correlation coefficient was 0.97 (95% confidence interval 0.9663-0.9678), with a two-tailed p-value of <0.0001. Conclusion and Relevance: The SpotOn is an accurate method that may enable non-invasive monitoring of core body temperature during TTM, although its precision is slightly worse than the pre-defined 0.5°C when compared to invasive esophageal probe.